2019
DOI: 10.3390/genes10100748
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Fecal Microbiota Composition Between Rheumatoid Arthritis and Osteoarthritis Patients

Abstract: The aim of this study was to investigate differences between the gut microbiota composition in patients with rheumatoid arthritis (RA) and those with osteoarthritis (OA). Stool samples from nine RA patients and nine OA patients were collected, and DNA was extracted. The gut microbiome was assessed using 16S rRNA gene amplicon sequencing. The structures and differences in the gut microbiome between RA and OA were analyzed. The analysis of diversity revealed no differences in the complexity of samples. The RA gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 41 publications
(45 reference statements)
6
53
0
Order By: Relevance
“…These findings are corroborated by earlier reports in the Indian sub-continenet TB patient population [ 46 ]; (b) Catenibacterium , is reported to be enriched in HIV-infected individuals [ 55 ]; (c) Bifidobacterium was enriched in the TB patient group in this study, a known opportunistic pathogen that causes bacteremia in immunocompromised patients, or those with a compromised intestinal barrier [ 56 ]. Other members of the family, Bifidobacteria , are known to carry genes capable of conferring antibiotic-resistance to anti-tubercular drugs [ 57 ]; (d) Eggerthella is an anaerobic gram-positive bacillus associated with polymicrobial intraabdominal infections [ 58 ]; (e) Catenibacterium , (f) Collinsella , and (g) Eggerthella , were found to be enriched in the gut microbiota of TB patients in this study, they are reported to be associated with rheumatoid arthritis, another inflammatory disease [ 59 , 60 ]; and (h) Burkholderia is associated with pneumonia-derived melioidosis [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are corroborated by earlier reports in the Indian sub-continenet TB patient population [ 46 ]; (b) Catenibacterium , is reported to be enriched in HIV-infected individuals [ 55 ]; (c) Bifidobacterium was enriched in the TB patient group in this study, a known opportunistic pathogen that causes bacteremia in immunocompromised patients, or those with a compromised intestinal barrier [ 56 ]. Other members of the family, Bifidobacteria , are known to carry genes capable of conferring antibiotic-resistance to anti-tubercular drugs [ 57 ]; (d) Eggerthella is an anaerobic gram-positive bacillus associated with polymicrobial intraabdominal infections [ 58 ]; (e) Catenibacterium , (f) Collinsella , and (g) Eggerthella , were found to be enriched in the gut microbiota of TB patients in this study, they are reported to be associated with rheumatoid arthritis, another inflammatory disease [ 59 , 60 ]; and (h) Burkholderia is associated with pneumonia-derived melioidosis [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 26‐28 ) In addition, Acidaminococcus was recently reported to be enriched in the stool of patients with rheumatoid arthritis, ankylosing spondylitis, and ulcerative colitis. ( 29,30 ) Although Acidaminococcus has not been previously associated with AIH, prior studies have shown that Veillonella , another member of the Negativicutes class, was enriched in patients with classical AIH and associated with disease activity. ( 21 ) In our cohort, there was no significant difference in serum primary and secondary bile acid profiles between patients with or without APAH.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this study did include individuals with undifferentiated arthritis (likely to include SpA patients) which represents progression of the disease phenotype beyond the pre-arthritis “at-risk” phase ( Alpizar-Rodriguez et al, 2019b ). Multiple studies describing various dysbiotic bacterial states associated with RA have been published, some demonstrating increased Prevotellaecae ( Maeda et al, 2016 ; Jeong et al, 2019 ; Lee et al, 2019 ; Rodrigues et al, 2019 ), some decreased prevotellaecae ( Vaahtovuo et al, 2008 ; Breban et al, 2017 ) and others attributing the dysbiosis to other organisms, such as Clostridiaceae ( Muñiz Pedrogo et al, 2019 ) Blautia , Akkermansia , and Clostridiales ( Chiang et al, 2019 ), lactobacilli ( Liu et al, 2013 ; Picchianti-Diamanti et al, 2018 ), Actinomyces , Eggerthella ( Chen et al, 2016 ; Forbes et al, 2018 ). Table 2 contains a summary of microbial perturbations found in RA.…”
Section: The Gut Microbiome and Ramentioning
confidence: 99%